Tabulated depth, azimuth, and plunge (dip) of fracture dip vectors measured in ODP Hole 118-735B - David Goldberg; Christina Broglia; Keir Becker (PANGAEA, 1991)
Geophysical logs recorded over 500 m in Hole 735B have been analyzed to identify the in-situ properties and the fracture permeability of basement rocks in the Atlantis II Fracture Zone. Although hydroxyl-bearing alteration minerals were found to be most abundant in the upper section of this hole, the highest permeabilities were also measured in this zone by packer tests. This interval corresponds to the presence of several open fractures imaged by the acoustic televiewer and to indications of fluid flow through transmissive fractures in the log responses. Negative temperature-gradient and large semblance anomalies were found to correlate well with the largest of the observed fracture zones near 40, 100-150, 200, and 264 mbsf. Although no stress-induced wellbore breakouts were observed in the televiewer images, most of the 70 identified fractures strike subparallel to the north-south fracture zone and dip steeply west-southwest. These fractures probably formed as a result of normal faulting on the transform side of the uplifted ridge, where Hole 735B was sited in the Atlantis II Fracture Zone, rather than as a direct result of horizontal plate-tectonic motion.
Supplement to: Goldberg, D et al. (1991): Fracturing, alteration, and permeability: in-situ properties in Hole 735B, Atlantis II fracture zone, Southwest Indian Ocean. In: Von Herzen, RP; Robinson, PT; et al. (eds.), Proceedings of the Ocean Drilling Program, Scientific Results, College Station, TX (Ocean Drilling Program), 118, 261-269, https://doi.org/10.2973/odp.proc.sr.118.144.1991